The kinetid structure of two oscarellid sponges (Class Homoscleromorpha) unveils plesiomorphies in kinetids of Homoscleromorpha–Calcarea lineage. Issue 4 (8th October 2020) - Pozdnyakov, Igor R.; Sokolova, Agniya M.; Ereskovsky, Alexander V.; Karpov, Sergey A.
Abstract: The structure of the kinetid (flagellar or ciliary apparatus) is known to be of phylogenetic significance in sponges (Phylum Porifera) and can provide information about evolutionary relationships. Here, we report on the larval kinetid structure of two closely related species, Oscarella lobularis and O. tuberculata (Homoscleromorpha, Oscarellidae). Cells belonging to the four previously recognized morphological regions (anterior pole, lateral zone, paracrystalline belt, and posterior pole) were studied. The cells of the paracrystalline belt have pear‐shaped nuclei with a paracrystalline inclusion connected to the roots of the kinetid. In the cells of other zones, the nucleus is separated from the kinetid, and the roots adjoined the Golgi apparatus only. In kinetids of the studied larval cells, we observed the accessory centriole arranged immediately under the kinetosome, and two unequal fibrillar roots. These features are unique for sponge larvae. Comparing kinetids of the Homoscleromorpha with those in its sister group, the Calcarea, we propose an ancestral composition for the kinetid in the lineage Calcarea + Homoscleromorpha. This proposed kinetid structure includes a kinetosome–nucleus link, striated roots, simple basal foot, orthogonal centriole, and a long transition zone of the flagellum. The position of the centriole under the kinetosome in homoscleromorph larvae and the stout fibrillar or microtubular bundle on the kinetosome in calcarean larvae might be the apomorphies of these groups.